Industry‐specific exchange rate volatility and intermediate goods trade in Asia. (16th January 2016) - Sato, Kiyotaka; Shimizu, Junko; Shrestha, Nagendra; Zhang, Shajuan
Abstract: This study empirically analyses the impact of industry‐specific real exchange rate volatility on intra‐Asian trade of intermediate goods at an industry level. In contrast to the recent studies, our empirical results reveal that the exchange rate volatility has significantly negative effect only on two industries: general machinery and electrical machinery. However, no significant effects are found on the intermediate goods trade of other machinery industries. Such different impacts of the exchange rate volatility across industries reflect the growing intra‐firm trade and the choice of invoice currency, which is related to the characteristics of the traded goods.